Enhancing creative performance among experienced newcomers: exploring the influence of knowledge exchange, learning goals, personality traits, and technostress - Linpei Song; Zhuang Ma (Humanities & Social Sciences Communications)
Abstract Digital firms often hire experienced newcomers (ENs) to bring in external knowledge and leverage their creativity for innovation. However, these newcomers still need context-specific and complementary knowledge from organizational insiders to achieve creative performance. Drawing on trait activation theory, this study examines (1) how learning goal orientation (LGO) and personality traits (openness to experience, conscientiousness, and agreeableness) predict experienced newcomers’ knowledge exchange, including acquisition (KA) and donation (KD), and (2) the association between knowledge exchange and creative performance. Our analyses of two-wave time-lagged data from 236 EN responses suggest that LGO, openness to experience, conscientiousness, and agreeableness positively influence KA and KD. We also found that KA and KD are positively associated with creative performance. However, technostress negatively moderates the relationships between openness to experience and KA, conscientiousness and KA, and agreeableness and KA, as well as the relationships between LGO and KD and agreeableness and KD. Our results contribute to the literature on EN recruitment for innovation in digital firms and have theoretical and practical implications for ENs’ creative performance, learning goal orientation, personality traits, knowledge exchange, and the use of technology to facilitate such exchange.